Clinicopathological study on patients presenting with obstructive jaundice - Shukla, Samir; Kharat, Prashant R.; Kumar, Krishna (International Surgery Journal, 2018)
Background: Obstructive jaundice is frequently encountered surgical disease in the practice. This study is aimed to analyse age and sex distribution and incidence of malignant or benign causes in patients presented with obstructive jaundice. Author thoroughly documented various clinical presentations in these patients, evaluated them for stage of disease and appropriate management modality available for that particular stage. Methods: This is observational study carried out in Department of General Surgery, Hamidia hospital Bhopal on 100 patients over period of 18 months from January 2016 to July 2017. Results: Obstructive jaundice is more prevalent in 5th and 6th decade of life and male to female ratio of 2:3. Abdominal pain (97%) and jaundice (81%) are two common presentations. Malignancy (68%) tends to be more common than benign disease (32%) and among malignancies periampullary carcinoma and advanced GB carcinoma occurs with equal frequency of 32 cases. 46% patients of malignant aetiology presented in stage IV disease. Curative resection for periampullary tumours by whipples procedure was possible in 14% patients. Operative palliation by triple bypass was done in 11% and others were managed by appropriate another palliative modality. Adeno-carcinoma is most common histopathological variant. Choledocholithiasis (28%) is most common benign aetiology and was managed successfully by choledocholithotomy and T-tube insertion. Conclusions: Awareness of common presenting symptoms of obstructive jaundice should be done so that the patient present early for diagnosis and curative surgery and thereby prolonged survival rate. Palliative procedures are commoner than curative resection due to late presentation.